Prostitution in Padang City 1891-1942 - Riska Putriani; Suriani (Journal of Indonesian History, 2025)
Socio-economic conditions ware the background to the emergence of protitution practices in the city of Padang in 1891-1942, This study examines socio-economic factors, and public health impacts including the pread of sexually transmitted diseases such as syphilis. This study aims to identify social and economics factors that drive the growth of prostitution in the city of Padang and analyze the Dutch government’s policies in overcoming the rampant practices of prostitution. Then reveal the impacts that arise from the practices of prostitution on public health including sexually transmitted diseases and how to overcome them. This study uses a qualitative approach with a historical mettod that includes primary and secondary data collection. Primary data taken in this study comes from the Besluit Archives which contain decrees regarding regulations related to prostitution in West Sumatra and East Sumatra. BGS 19 November 1890, No. 2812, BGS. 19 March 1891 No. 617, CL. 29 August 1891 No. 16452 and CL. 22 November 1889, No. 21793. While secondary sources in the from of books, theses, articles, YouTobe or orther online media can be accessed via the city of Padang during the Duth colonial era. The results of the study indicate that the practice of prostitution in Padang City in influenced by the social-economic conditions of the community, where proverty and lack of employment encourage some women to engage in prostitution as source of livelihood. In addition, the colonial government’s policies tend to be ambivalent in both regulating and curbing this practice, creating complex dynamics. The colonial government implemented regulations aimed at conrolling and monitoring the practice of prostittution. Policies often aimed the control the spread of sexually transmitted diseaseses with a particular focus on syphilis which was a major health problem during taht priod.